Different mechanisms in periventricular and deep white matter hyperintensities in old subjects - Cai, Jinsong; Sun, Jianzhong; Chen, Haiyan; Chen, Ying; Zhou, Ying; Lou, Min; Yu, Risheng (Frontiers in Aging Neuroscience, 2022)
Objective: Although multiple evidence has suggested that there are different mechanisms in periventricular white matter hyperintensities (PWMHs) and deep white matter hyperintensities (DWMHs), the exact mechanism remains uncertain. Methods: We reviewed clinical and imaging data of old participants from a local She Ethnic group. We assessed the cerebral blood flow of white matter (WM-CBF) on arterial spin-labeling, deep medullary veins (DMVs) visual score on susceptibility-weighted imaging, and index for diffusion tensor image analysis along the perivascular space (ALPS index) indicating glymphatic function on diffusion tensor imaging. Furthermore, we investigated their relationships with volumes of PWMHs and DWMHs. Results: A total of 152 subjects were included, with the average age of 63 ± 8 years old. We found that higher age and history of hypertension were independently related to higher volumes of both PWMHs and DWMHs (all p<0.05). Lower ALPS index was independently associated with higher PWMHs volumes (β=0.305, p<0.001), and this relationship was accounted for by the indirect pathway via DMVs score (β=0.176, p=0.017). Both lower ALPS index and WM-CBF were independently risk factors for higher DWMHs volumes (β=-0.146, p=0.041; β=-0.147, p=0.036). Conclusions: Our study indicated that there were different mechanisms in PWMHs and DWMHs. PWMHs was mainly attributed to the damage of veins due to the dysfunction of glymphatic pathway, while DWMHs could be affected by both ischemia-hypoperfusion and dysfunction of glymphatic pathway. Advances in knowledge: The relationship of glymphatic dysfunction and PWMHs might be accounted for by the indirect pathway via venous abnormalities, and glymphatic dysfunction and lower CBF in white mater were independently risk factors for DWMHs.